(untitled) (Economia Aplicada, 1998)
Despite its general character, the harmonization of economic policies presents two problems that need to be considered. One is the initial degree of uniformity in the behavior of the economies involved in the economic integration process. The other, the way the policies have to be implemented in the view of the whole. This paper provides a brief overview of both problems in MERCOSUR.